Gene therapy in sport - Trent, R. J.; Alexander, I. E. (British Journal of Sports Medicine, 2005)
Human gene therapy involves the insertion of DNA (or RNA) into somatic cells to produce a therapeutic effect. Gene therapy was first envisaged as an approach to treating genetic disorders. In this scenario, missing or mutant genes could be replaced or repaired. Today, gene therapy has broader applications, with trials covering many clinical problems including genetic diseases, cancer, infections such as HIV, and degenerative diseases.